KUDETA REDAKSIONAL DALAM PROSES LEGISLASI NASIONAL - Ni Ketut Wiratny; Ni Luh Putu Geney Sri Kusuma Dewi (Jurnal Aktual Justice, 2020)
It is undeniable that there are problems in the legislative process in Indonesia, one of which is tampering with articles or editorial coups. In fact, this illegal practice can occur in three conditions. First, it occurs in the draft produced by a special committee or commission before it is brought to the plenary session of the DPR. The second occurred after the DPR plenary session. The third is the most difficult to control, if an editorial coup is carried out by the government before it is passed by the president, then it is promulgated in the State Gazette. At this stage, when the bill is in the hands of the government, the DPR finds it difficult to check. Given that this is the final stage, the possibility of a new editorial coup has been traced after it was implemented. As a product that is agreed upon in the highest forum (plenary session) and is the result of joint legislative-executive agreement, the slightest change made is haram. This research is a normative juridical research by conducting literature studies and analyzing secondary data. The results of this study indicate that if it is true that there is an editorial coup in the legislative process, the legal product has formal and material defects which can be canceled through the right to test exercised by the Constitutional Court.